Development of Batik Modul Based on Local Culture of North Sumatra, Indonesia - Farihah Farihah; Halimul Bahri; Surniati Chalid; Yudhistira Anggraini (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2022)
This study aims to develop teaching materials in the form of local culture-based batik moduls that can be used as the development of Medan batik motives at Ardhina Batik Medan. This study uses the Research and Development (R&D) research method and the research model uses the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The results of the study show that the results of the modul feasibility test according to 6 experts. The results of the data analysis carried out stated that the batik modul based on the local culture of North Sumatra at Ardhina Batik Medan was suitable for use with the